2020
DOI: 10.1051/matecconf/202030500061
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals from a contaminated soil using phytoremediation

Abstract: Environment pollution with heavy metals, can be a cause of the industrialization activities and technological processes, and has become an important issue. Soil contamination due to natural or anthropogenic causes (such as mining, smelting, warfare and military training, electronic industries, fossil fuel consumption, waste disposal, agrochemical use and irrigation) is a major environmental hazard. Various remediation techniques have been highlighted to clean or restore soils contaminated with heavy metals suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A study from Tatu et al [35] revealed that mustard plants grown in heavy-metalcontaminated soil accumulated very high levels of Cu, Pb, and Zn in their roots, stems, and leaves. The levels of these metals in the plant tissues surpassed the concentrations found in the soil.…”
Section: Total Heavy Metal Concentrations In Soil and Mustardmentioning
confidence: 99%
“…A study from Tatu et al [35] revealed that mustard plants grown in heavy-metalcontaminated soil accumulated very high levels of Cu, Pb, and Zn in their roots, stems, and leaves. The levels of these metals in the plant tissues surpassed the concentrations found in the soil.…”
Section: Total Heavy Metal Concentrations In Soil and Mustardmentioning
confidence: 99%
“…In bioenergy production, plant biomass can yield energy through various methods, such as anaerobic digestion, pyrolysis, or combustion. This approach can help reduce the reliance on fossil fuels and provide a renewable energy source [ 32 ].…”
Section: Advancements In Research To Address the Problems And Challengesmentioning
confidence: 99%
“…Additionally, effective communication and community engagement are crucial for ensuring the success of soil remediation efforts. It is essential to involve local communities in designing and implementing soil remediation strategies and to provide them with information about the risks associated with contaminated soil and the potential benefits of remediation [ 32 ]. The main effects of soil contamination on sustainable development goals are shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Even if they are considered as a non-hyperaccumulating species, these plants are able to grow quickly and produce a high amount of biomass, which are important elements in phytoremediation [53,54]. It can be said that, due to the production of a large amount of biomass, the overall accumulation of phytoextractor plants is close to that of hyperaccumulators [55]. Moreover, the plants of the Brasicaceae family are able to produce high levels of glutathione and phytochelatins, which are significant metabolites, assuring plant growth under metal stress conditions [53].…”
Section: Introductionmentioning
confidence: 99%